Factors affecting attitudes towards fruits and vegetables consumption on YouTube: a conceptual paper / Nur Shahafiqah Nadiah Jaffery, Sharifah Nurafizah Syed Annuar and Joseph Alagiaraj Thamburaj - Jaffery, Nur Shahafiqah Nadiah; Syed Annuar, Sharifah Nurafizah; Thamburaj, Joseph Alagiaraj (UiTM Cawangan Johor, 2020)
Given the rapid technological advancement, social media and communication devices continue to grow exponentially. One of them is YouTube, which is a public video-sharing website where people can experience varying degrees of engagement with videos, ranging from casual viewing to sharing videos to maintain social relationships. Based on fruits and vegetables consumption, this study analyzes how YouTube participants attitudes toward fruits and vegetables consumption in Malaysia. This study includes YouTube Advertising; perceived credibility, perceived usefulness, perceived video characteristics, number of views, comments, likes and replies and attitude among university students. The Tripartite Attitude Model is adapted as to provide theoretical base to explain specific on cognitive, affective and conation. This provides better understanding on attitude and fruits and vegetables consumption among undergraduate students in Malaysia. This conceptual paper contributes to YouTube studies in non-profit settings with a theoretical stance.